Evaluation of the Effect of Fixed Anterior Biteplane Treatment on Temporomandibular Joint in Patients with Deep Bite - Bengisu Akarsu Güven; Semra Ciğer (Galenos Yayinevi, 2020)
Objective:To investigate the effects of fixed anterior biteplane treatment on temporomandibular joint in deep bite patients.Methods:The sample comprised 17 Class II patients with deep bite and decreased lower anterior facial height. The average patient age was 9.9±0.9 years. Transcranial temporomandibular joint radiographs were obtained from the subjects before (T0) and after fixed anterior biteplane treatment (T1). Anterior joint space, posterior joint space, superior joint space, anteroposterior thickness of the condylar head, vertical height of the articular fossa, and the articular fossa slope were measured on temporomandibular joint radiographs to evaluate the position of the mandibular condyles in the glenoid fossa.Results:The average treatment duration was 8.5±2.1 months. Slope of the articular fossa, vertical height of the articular fossa, anteroposterior thickness of the condyle, posterior joint space, superior joint space, and anterior joint space showed no statistically significant difference between T0 and T1 (p>0.05).Conclusion:Fixed anterior biteplane appliance treatment did not change the condyle fossa relationship in Class II deep bite patients at the time of appliance removal.